Perubahan Agama Minahasa dan Kekristenan dalam Konstruksi Perjumpaan Simbol Sakral pada Ritual di Watu Pinawetengan - Hun Johanis A. Pinatik; Izak Y. M. Lattu; Rama Tulus Pilakoannu (IAKN Ambon, 2021)
This article aims to explore the conversion of Minahasa and Christianity religion through mutually constructed efforts carried out by the community of ritual practitioners in Watu Pinawetengan. This research focuses on the mutual change between Minahasa religion and Christianity in rituals through the construction of a symbolic encounter by the ritual-playing community at Watu Pinawetengan. For ritual practitioners, Watu Pinawetengan is a sacred place Tou Minahasa (Minahasa man) that is located in North Sulawesi Province, Minahasa Regency. Individuals in a community construct the meaning of each symbol, thus creating a paradigm of religion. Sacred symbols refer to the essence of a belief in religion, so it is crucial in describing the existence of a religion. The data is taken through the use of qualitative methods by conducting observations, interviews, library studies, and documentary studies. The findings of this study show that changes in sacred symbols in rituals have been constructed in Minahasa and Christian discourses, resulting in a mutual change in both religions. Change occurs dialectically and is strengthened by the legitimacy of the ancestral spirit.AbstrakArtikel ini bertujuan untuk menggali perubahan agama Minahasa dan Kristen melalui upaya saling mengonstruksi yang dilakukan oleh komunitas pelaku ritual di Watu Pinawetengan. Fokus penelitian pada perubahan bersama, antara agama Minahasa dan Kristen dalam ritual melalui konstruksi perjumpaan simbol oleh komunitas pelaku ritual di Watu Pinawetengan. Bagi pelaku ritual, Watu Pinawetengan merupakan tempat sakral Tou Minahasa (manusia Minahasa) yang berada di Provinsi Sulawesi Utara, Kabupaten Minahasa. Individu-individu dalam komunitas mengonstruksi makna dari setiap simbol sehingga menciptakan paradigma fundamen tentang agama. Simbol sakral merujuk pada esensi dari suatu kepercayaan dalam agama, sehingga bersifat krusial dalam menggambarkan eksistensi suatu agama. Data diambil melalui penggunaan metode kualitatif dengan melakukan observasi, wawancara, studi pustaka, dan studi dokumenter. Temuan dari studi ini memperlihatkan perubahan simbol sakral dalam ritual telah dikonstruksi dalam diskursus agama Minahasa dan Kristen, sehingga mengakibatkan perubahan bersama pada kedua agama tersebut. Perubahan terjadi secara dialektis dan diperkuat dengan legitimasi roh leluhur.Â